2020
DOI: 10.3390/ijms21197218
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Adenosine A3 Receptor Inhibits Microglia Reactivity Elicited by Elevated Pressure

Abstract: Glaucoma is a progressive chronic retinal degenerative disease and a leading cause of global irreversible blindness, characterized by optic nerve damage and retinal ganglion cell (RGC) death. Elevated intraocular pressure (IOP) is a main risk factor of glaucoma. Neuroinflammation plays an important role in glaucoma. We have been demonstrating that elevated pressure triggers microglia reactivity that contribute to the loss of RGCs. Adenosine, acting on adenosine receptors, is a crucial modulator of microglia ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 48 publications
(92 reference statements)
0
8
0
Order By: Relevance
“…In the CNS, the P2X7 receptor is preferentially located on microglia ( Illes, 2020 ). Besides that, several authors have also been reported the expression of P1 receptors in microglia, describing ADO as a crucial modulator of microglia phenotype of CNS pathologies, including cancer ( Hammarberg et al, 2003 ; Synowitz et al, 2006 ; Ferreira-Silva et al, 2020 ).…”
Section: Purinergic Signaling In Astrocytes: From Adenosine Triphosphate To Adenosinementioning
confidence: 99%
“…In the CNS, the P2X7 receptor is preferentially located on microglia ( Illes, 2020 ). Besides that, several authors have also been reported the expression of P1 receptors in microglia, describing ADO as a crucial modulator of microglia phenotype of CNS pathologies, including cancer ( Hammarberg et al, 2003 ; Synowitz et al, 2006 ; Ferreira-Silva et al, 2020 ).…”
Section: Purinergic Signaling In Astrocytes: From Adenosine Triphosphate To Adenosinementioning
confidence: 99%
“…A reduction of microglia activation was also observed stimulating A 3 ARs with the agonist IB-MECA, an effect likely underlining their antinociceptive action [ 172 ]. The selective A 3 AR agonist 2-Cl-IB-MECA was effective in controlling microglia reactivity induced by elevated hydrostatic pressure, with potential positive repercussions in glaucoma [ 173 ]. In a model of subarachnoid hemorrhage, 2-CI-IB-MECA markedly directed microglia towards the M2, or more precisely M(IL-4) phenotype, reduced inflammation, and improved neurological dysfunction [ 174 ].…”
Section: Neuroinflammationmentioning
confidence: 99%
“…Blocking microglial A2A R prevents microglial cell response to elevated pressure and it is sufficient to protect retinal cells from elevated pressure-induced death ( Aires et al, 2019 ). Another study found activation of Adenosine A (3) receptor could hinder the microglia reactivity ( Ferreira-Silva et al, 2020 ), attenuated the impairment in retrograde axonal transport, and afford protection against glaucomatous degeneration. In addition, P2X7 receptor antagonist protects retinal ganglion cells by inhibiting microglial activation in a rat chronic ocular hypertension model ( Dong et al, 2018 ).…”
Section: Neuroimmunitymentioning
confidence: 99%